PENDAMPING PERSALINAN SEBAGAI PENGURANG RASA NYERI SAAT BERSALIN DI RS MARGONO SOEKARDJO PURWOKERTO - ., Defiany; ., Sumarni; Febriani, Hendrisita; Fatonah, Yulinda; Erlyta, Nia Noor (Bidan Prada, 2013)
ABSTRACT: LABOR COMPANION AS A REDUCTION OF PAIN DURING LABOR AT MARGONO SOEKARDJO HOSPITAL IN PURWOKERTO. Labor is spending the products of conception that is a baby and placenta frommother uterus with pain. Many method was doing to decrease the pain during labor, such asthe physical therapy, pharmacology until the massage technique. If the application and thetechnique use was error, it is the aim to reduce the pain won’t be reached, even it will make more pain than before. Therefore, will more effective and efficient if the labor pain of maternal reduced with affect maternal psychological. One of the way affect maternalpsychological is bring the labor companion who highly desirable and trustworthy by thematernal. Objective : Purpose of the study is to analyze influence of the presence of labor companionas a reduction of pain during labor. Method : This study use the analytic research method with cross sectional approach, takinginto 30 maternal active phase of the first stage. The sampling technique use the accidental sampling. The collection of data obtained from anamnesis and observation with data analysisusing the chi square test. Result : The majority of respondent was accompanied during labor and just feel a little pain. There is a relationship between the presence of labor companion with reduction of painduring labor, it’s proven from ? value < ? (0,002 < 0,05). Conclusion : There is a relationship between the presence of labor companion withreduction of pain during labor. Keywords: Labor, Labor Pain, Labor Companion